Is information openness important for innovation infrastructure? Research of technoparks in Moscow. - Tyurchev, Kirill (Innovation Journal, 2022)
The creation and development of innovative infrastructure allows the economic development to be stimulated. A common form of such infrastructure is technology parks (technoparks). In recent years, the largest network of technoparks in the world has been developed in Moscow. Its purpose is to test the hypothesis that there is a relationship between their information openness and the operational performance of their management companies. The results obtained suggest that there is no significant statistical relationship between these indicators. The article proposes measures for increased information openness and transparency of technology parks, which is a current trend in the field of innovation policy in developed countries. In addition, the article discusses the threats and risks for technology parks and local authorities associated with a low level of information openness of the innovation infrastructure.